Association of Smoking with Total Oxidant and Antioxidant Levels in Breast Milk - Nesibe Yildiz; Adnan Yilmaz (Makara Journal of Health Research, 2022)
Background: Breast milk is a natural food that contains all the fluids, energy, and nutrients necessary for the optimum growth and development of newborns. Smoking is a public health problem that has harmful effects on the mother and baby. This study aimed to examine the association of exposure to smoking with total oxidant status (TOS) and total antioxidant status (TAS) in breast milk.